Functional Regeneration of Brachial Sensory Afferents to the Brainstem. - Wong, Laura. (2017)
Abstract: Spinal cord injury leads to devastating paralysis and paresis, in large part because damaged axons in the central nervous system fail to regenerate. Recovery following a spinal cord injury will require axons to restore synaptic connectivity with denervated targets several centimeters from the site of injury. This will require therapeutic agents that promote regeneration across long distances. Here, we report that brief systemic artemin treatment promotes regeneration of sensory axons to the brainstem following brachial dorsal root crush in an adult rat. Axon regeneration to the brainstem takes more than three months, consistent with slow growth across the three to four centimeter distance to reach the brainstem. Artemin not only stimulates robust regeneration of large, myelinated sensory axons to the brainstem, but it also promotes functional reinnervation of the appropriate target region, the cuneate nucleus. Remarkably, axons regenerate appropriately in the dorsal columns and establish connections with the correct nucleus in the brainstem without the addition of exogenous guidance molecules. Artemin signals primarily through the RET tyrosine kinase, an interaction that requires the non-signaling co-receptor GFRα3. Previous studies report limited GFRα3 expression on large sensory neurons, suggesting that artemin could not signal in these neurons. Our findings, however, demonstrate that artemin promotes robust regeneration of large, myelinated sensory afferents suggesting some manner by which artemin signals in these neurons. Using a cell sorting technique, we demonstrated that the expression of GFRα3 is similar in myelinated and unmyelinated adult sensory neurons. This suggests that artemin likely induces long-distance regeneration by binding GFRα3 and RET. Although artemin is delivered for just two-weeks, regeneration to the brainstem requires more than three months, suggesting that brief trophic support may initiate intrinsic growth programs that remain active until targets are reached. Artemin may therefore represent a promising therapy for targeted sensory axon regeneration and functional reinnervation after spinal cord injury. In addition, understanding the mechanism by which artemin promotes regeneration may provide important insights into the development of future therapeutics to promote recovery following spinal cord injury.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Neuroscience.; Advisor: Eric Frank.; Committee: James Schwob, Kathleen Dunlab, Daniel Jay, and Zhigang He.; Keywords: Neurosciences, and Physiology.